Komunikasi Pemasaran Terpadu pada Brand Skincare Lokal: Analisis Komparatif Camille Beauty dan Somethinc di Instagram dan TikTok - Wening Afqoh Fhaizyah; Lukman Hakim (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The pervasive role of social media in Indonesia's skincare industry necessitates an in-depth understanding of integrated marketing communication (IMC) strategies. This study investigates how two leading local skincare brands, Camille Beauty and Somethinc, implement Duncan’s (2005) eight IMC tools across Instagram and TikTok platforms and assesses their impact on brand awareness and sales growth. Using a descriptive qualitative approach with a comparative case study design, data were gathered through digital observation of 3,230 posts, consumer reviews, and brand interactions from 2018–2025. Analysis followed Miles and Huberman’s interactive model, incorporating data reduction, comparative matrix presentation, and member-check validation. Key findings reveal: (1) Camille Beauty leveraged TikTok Live for personal selling (achieving 3,482 conversions/session), (2) Somethinc dominated event sponsorships (12.4% engagement vs. industry average 5.7%), and (3) IMC integration drove Camille Beauty’s 42% sales growth (2023) and Somethinc’s 341K+ TikTok Shop units. The study concludes that platform-specific IMC differentiation—TikTok for direct conversions, Instagram for brand storytelling—is critical for competitive advantage. These insights offer actionable frameworks for skincare brands navigating Indonesia’s hypercompetitive digital landscape.